The Role of science, technology and innovation in increasing substantially the share of renewable energy by 2030 (UN US, 2018)
Focuses on how science, technology and innovation can help increase the share of renewable energy in the global energy mix. Reviews the latest trends in the use of renewable energy technologies, identifies the barriers and drivers of their deployment and provides an overview of emerging technologies.
Keywords: RENEWABLE ENERGY SOURCES